Credit constraints and exports: Evidence for German manufacturing enterprises - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
This study uses newly available enterprise level data for firms from manufacturing industries in Germany to test for the link between credit constraints, measured by a credit rating score from the leading credit rating agency Creditreform, and exports. In line with hypotheses from theoretical model we find a positive link between a better credit rating score of a firm and both the probability that the firm is an exporter and a higher share of exports in total sales. This link, though statistically highly significant, is not very strong from an economic point of view. While empirical evidence for the hypothesis that credit constrained firms are less likely to start to export is at best weak, we find no evidence for a statistically significant difference in credit rating scores between firms that stopped to export and firms that continued to export.
Keywords: F14; 330; Credit constraints; exports; Germany; Verschuldungsrestriktion; Exportindustrie; Verarbeitendes Gewerbe; Export; Deutschland